Analisis Kaidah Al-Umuru Bi Maqasidiha dan Penerapannya dalam Ekonomi Islam - Indah Dwi Agustina Dewi; Raras Elok Manikam Putri Pribadi; Azka Nabilatuz Zahra; Zaskia Syafa Azizah; Salsabila Nur Syifa’; Naysila Khoirotun Nisa; Taufiq Kurniawan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
The principle of "Al-Umuru Bi Maqasidiha," meaning "everything depends on its purpose," is one of the main principles of Islamic law that plays a crucial role in Islamic economic practices. This research aims to outline the meaning, legal basis, branches, and application of this principle in modern economic activities. The method used is a literature review, examining the Quran, Hadith, the opinions of scholars, and contemporary studies related to Islamic economics. The results of the study indicate that intention is a key factor in determining the validity or invalidity of an act, both in worship and transactions. This principle is relevant to addressing contemporary transaction developments, such as Islamic banking, fintech, and digital investment instruments, by emphasizing objectives aligned with the maqasid al-shariah (Islamic principles). The evolving branches of this principle emphasize the role of intention in distinguishing between custom and worship, establishing the validity of contracts, and transforming permissible activities into acts of worship. Its application in Islamic economics encompasses transaction contracts, asset management (mal), and Islamic banking practices, all of which are directed toward achieving benefits and preventing harm. In conclusion, the principle of Al-Umuru Bi Maqasidiha (The Principle of Proper Conduct and the Principle of Good Conduct) is highly urgent in building an Islamic economic system that is just, imbued with integrity, and oriented toward blessings.